2010
DOI: 10.1177/0022146510383498
|View full text |Cite
|
Sign up to set email alerts
|

Social Conditions as Fundamental Causes of Health Inequalities: Theory, Evidence, and Policy Implications

Abstract: Link and Phelan (1995) developed the theory of fundamental causes to explain why the association between socioeconomic status (SES) and mortality has persisted despite radical changes in the diseases and risk factors that are presumed to explain it. They proposed that the enduring association results because SES embodies an array of resources, such as money, knowledge, prestige, power, and beneficial social connections that protect health no matter what mechanisms are relevant at any given time. In this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
1,543
7
31

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,954 publications
(1,644 citation statements)
references
References 33 publications
63
1,543
7
31
Order By: Relevance
“…In contrast to sex differences, previous studies have suggested that biological differences between racial groups contribute little to the differences in outcomes, which are driven largely by differences in socioeconomic well‐being and quality of care at hospitals where black patients seek care 6, 26, 27, 28, 29, 30, 31, 32. The continued high post‐CABG mortality in black patients merits further investments in targeting hospital‐level quality improvement interventions, as well as in strengthening systems for transitions of care outside the hospital and developing community support interventions that support this unique sociocultural group.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to sex differences, previous studies have suggested that biological differences between racial groups contribute little to the differences in outcomes, which are driven largely by differences in socioeconomic well‐being and quality of care at hospitals where black patients seek care 6, 26, 27, 28, 29, 30, 31, 32. The continued high post‐CABG mortality in black patients merits further investments in targeting hospital‐level quality improvement interventions, as well as in strengthening systems for transitions of care outside the hospital and developing community support interventions that support this unique sociocultural group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that people who possess the most resources, such as knowledge, money and social connections, and have the best capacity to utilize them in a flexible manner, have the best prerequisites for preventing risks and thus avoiding adverse health outcomes, such as diseases or disabilities (Phelan, Link & Tehranifar 2010). People with more resources also have a wider range of choices they can select from in order to adapt to risks (Satariano 2006).…”
Section: Theory Of Fundamental Causesmentioning
confidence: 99%
“…These factors are seen as either having a direct material impact on the capacity of families to offer children a good developmental experience or as indirectly causing stresses that affect parents' ability to function effectively. Detrimental consequences of stress, such as excessive alcohol or substance use, exposure to intimate partner violence or poor mental health, can be seen as secondary to fundamental causes (Bywaters, 2015a;Phelan et al, 2010). In some cases such structural difficulties cross generations increasing the likelihood of a range of behavioural and health factors damaging to family life.…”
Section: Introductionmentioning
confidence: 99%